2001
DOI: 10.1053/euhj.2001.2891
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of left atrial appendage flow velocity for predicting of cardioversion success in patients with non-valvular atrial fibrillation*1

Abstract: In patients with non-valvular atrial fibrillation, measurement of the left atrial appendage flow velocity profile by transoesophageal echocardiography before cardioversion provides valuable information for prediction of cardioversion outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…Although there is increasing evidence of the LAA importance as a trigger for atrial arrhythmias, the literature is scarce on the mechanisms and factors that may contribute to it. Previous studies have demonstrated the value of LAA flow velocity in the prediction of sinus rhythm maintenance after electrical cardioversion and, recently, Kanda et al described an association between low LAA flow velocity and AF recurrence after catheter ablation in patients with persistent AF [28][29][30]. The current research suggests that LAA volume may be a surrogate of increased LAA arrhythmogenicity, similar to what happens with the LA volume: an enlarged LA is associated with electrical remodelling, which provides an arrhythmogenic substrate for AF triggers [31].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is increasing evidence of the LAA importance as a trigger for atrial arrhythmias, the literature is scarce on the mechanisms and factors that may contribute to it. Previous studies have demonstrated the value of LAA flow velocity in the prediction of sinus rhythm maintenance after electrical cardioversion and, recently, Kanda et al described an association between low LAA flow velocity and AF recurrence after catheter ablation in patients with persistent AF [28][29][30]. The current research suggests that LAA volume may be a surrogate of increased LAA arrhythmogenicity, similar to what happens with the LA volume: an enlarged LA is associated with electrical remodelling, which provides an arrhythmogenic substrate for AF triggers [31].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have suggested that cardioversion success of atrial fibrillation may be predicted by the assessment of LAA flow velocity before cardioversion, but some methodological problems have weaken the outcomes of these studies, and moreover, some other studies have not confirmed their findings (Mitusch et al 1995;Verhost et al 1997). Palinkas et al (2001) studied the role of LAA flow velocity by TEE for prediction of cardioversion outcome before cardioversion in patients with nonvalvular atrial fibrillation. Their prospective multicenter study consisted of larger sample size and strict selection criteria (duration of atrial fibrillation was less than 1 year).…”
Section: Discussionmentioning
confidence: 99%
“…LAA flow velocity may also represent LAA contractile function. Recent studies have suggested that the conversion from atrial fibrillation to sinus rhythm may be predicted by evaluating LAA velocities before cardioversion (Mitusch et al 1995;Tabata et al 1997;Palinkas et al 2001). However, there have been conflicting data in the literature (Perez et al 1997;Verhost et al 1997).…”
Section: © 2006 Tohoku University Medical Pressmentioning
confidence: 99%
“…[8][9][10][11][12] The relationship between the LAA-V and cardiac rhythm has been described in patients who underwent cardioversion of persistent AF. [16][17][18][19][20] If LA function was maintained at a certain level, patients were more easily kept in SR after PV-cryo. However, we sometimes encountered patients with AF in which an LA contraction could hardly be recognized.…”
Section: Relation Between the Laa-v And Long-term Resultsmentioning
confidence: 99%
“…However, our subjects included some with a long AF-D (>10 years; n=18, 18% of all patients), large LAD (=60 mm; n=28, 28% of all patients), or low LAA-V (=20 cm/s; n=38, 38% of all patients). Long-standing AF, 14,15 a large left atrium, 14,15 and low LAA-V [16][17][18][19][20] all are considered negative predictive factors for both recovery and maintenance of SR.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%